THE Effect of Short-Term and Long-Term Learning in Quality Management and Innovation - Siti Patmawati; Valin Mertianti Dewi; Masduki Asbari (Journal of Information Systems and Management (JISMA), 2023)
Quality oriented management change and innovation is the main strategy for the company. The implementation of quality improvement and innovation has an organizational and managerial role significant technical, and may also involve significant delays before both are realized. In this literature study, we used a descriptive method with a qualitative approach. Our study highlights the short-term and long-term beneficial effects of QIM (Quality improvement management) adoption on product innovation performance. In addition, we found evidence of complementarity and learning effects using QIM adoption. Results show that maximizing innovation returns and improving quality requires consideration of Soft and Hard properties Individual QIM and the timing and sequence of their application. In addition, we find evidence of complementarity and learning effects using QIM adoption. Our results suggest that maximizing innovation returns and improving quality requires the severity of individual QIM and the timing and sequence of their implementation .